Transient synchronization stability mechanism of PMSG with additional inertia control - Yayao Zhang; Meng Zhan (IET Renewable Power Generation)
Abstract Synchronous stability is crucial for the safety and operation of AC power systems. However, most of the current researches focused on the stability of grid‐connected converters, and that of renewable equipment still lacked. In this article, the impact of the additional inertia control (AIC) on the permanent magnet synchronous generator (PMSG) is studied. It is found that with the AIC, the machine‐side converter dynamics of the PMSG cannot be ignored, and the system dominant dynamics shifts from the electromagnetic to electromechanical timescales. This article develops a simplified model for the single‐PMSG infinite‐bus system with the AIC within the electromechanical timescale, and reveals the transient synchronization stability mechanism from three aspects: the machine‐network interface, transient dominant variable, and interaction between the synchronization loop and the power imbalance loop. Finally, this article analyzes the swing characteristics of the PMSG system, and uncovers the relationship between the energy transmission and synchronization. These findings are supported by wide experimental verification and can provide the deeper physical insight and theoretical basis for the transient synchronous stability analysis of renewable‐dominated new‐type power systems.